Harnessing web-based contrastive instruction to address English relative clause accuracy and subject-object asymmetry. (October 2019) - Lucas, Matt; Takeuchi, Osamu
Abstract: This exploratory study set out to investigate two principal aims: (1) the general effect of contrastive linguistic input delivered via an online medium on the subsequent written accuracy of subject and object restrictive relative clauses; and (2) the specific effect of administering such instruction in equal proportion on both clause types in light of markedness theory (that purports easier structures will naturally improve when harder ones are afforded more pedagogical attention). To meet these aims, a total of 156 Japanese EFL university learners were divided into two groups: an experimental group that was exposed to four web-based treatment sessions over four consecutive weeks, and a control group that continued with their regular studies without any contrastive input. Statistical analyses of pre, post, and delayed posttest performances demonstrated that the intervention led to positive learning outcomes for overall clause accuracy. However, in spite of markedness theory predicting a greater improvement for subject relative clauses (which are generally deemed easier), the reverse was found to be true. Interpretations for this unexpected finding are provided, along with pedagogical implications and future directions for related research.